Inclusive wealth report 2018: Measuring progress towards sustainability - Shunsuke Managi; Pushpam Kumar (Routledge, 2018)
The Inclusive Wealth Index provides important insights into long-term economic growth and human well-being. The Index measures the wealth of nations through a comprehensive analysis of a country's productive base and the country's wealth in terms of progress, well-being and long-term sustainability. It measures all assets which human well-being is based upon, in particular, produced, human and natural capital to create and maintain human well-being over time. The Open Access version of this book, available at http://www.taylorfrancis.com/books/9781351002080, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.
Keywords: 330